Reducing estimated tail biting risk in German weaner pigs using a management tool. (December 2019) - Grümpel, A.; Krieter, J.; Dippel, S.
Highlights: The use of the management tool SchwIP reduced risk for tail biting. The tool increased the farmers' awareness of risk factors for and occurrences of tail biting. Individual circumstances and types of changes varied between farms, reflecting the multifactorial character of tail biting. Abstract: The tail biting management tool 'SchwIP' was developed to analyse estimated farm individual risk for tail biting and to support farmers to reduce risk. The risk factors included in SchwIP had been weighted by 61 experts regarding their strength of influence on tail biting. SchwIP was applied on 21 conventional farms throughout Germany that kept weaner pigs in closed barns. All farms were assessed with the SchwIP questionnaire and received farm-individual feedback and advice on how to reduce tail biting risk. There were no control farms with assessment only, because asking questions could raise awareness thus triggering improvements. Each farm was visited three times at 6 monthly intervals. Risk factor data collected on farms were replaced with the corresponding expert weighting, and weightings were then standardised to a range of 0 – 1 across all farms and visits. All standardised risks were summarised per farm and visit. From this, within-farm differences in farm risk sums between visit 1 and 2 (ΔRS12), 2 and 3 (ΔRS23) and 1 and 3 (ΔRS13), and the association between changes in single risk factors with ΔRS, were calculated. Farm risk sums significantly decreased from visit 1 to visit 2 and 3, respectively, but not from visit 2 to visit 3. Change in farm risk sums between visit 1 and 2 was significantly correlated with 59 factors; ΔRS23 with 54 factors; and ΔRS13 with 57 factors. Eighteen factors were significantly associated with all three ΔRS. The management tool SchwIP contributed to a reduction in estimated risk for tail biting in weaners after the first visit. There was no apparent pattern of changes in risk factors on the farms, which underlines the multifactorial nature of tail biting. Further on-farm research on tail biting risk factors and tail lesions is needed to better understand the complex relationship.